2005
DOI: 10.1111/j.1365-2141.2005.05641.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose idarubicin, cyclophosphamide and melphalan as conditioning for autologous stem cell transplantation increases treatment‐related mortality in patients with multiple myeloma: results of a randomised study

Abstract: SummaryWe conducted a randomised trial comparing an intensified versus a standard conditioning regimen for high-dose chemotherapy followed by autologous stem-cell transplantation in patients with multiple myeloma. In this study, 56 patients were randomly assigned for high-dose therapy with melphalan 200 mg/m 2 or with idarubicin 42 mg/m 2 , melphalan 200 mg/m 2 and cyclophosphamide 120 mg/kg. The primary objective was response rate. Acute toxicity, mainly because of infections, was higher in the intensified tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…24 Dose intensification of conditioning regimen can be potentially dangerous: a study in 56 MM patients added idarubicin and CY to melphalan 200 mg/m 2 , but this was followed by a treatment-related mortality of 20% (vs 0% in the standard arm with melphalan 200 mg/m 2 ), which lead to early discontinuation of the study. 25 Another investigational strategy has been to increase the dose of single-agent melphalan to 4200 mg/m 2 with the concurrent use of the cytoprotective agent amifostine, 26,27 but data are too preliminary to justify the use of this approach in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…24 Dose intensification of conditioning regimen can be potentially dangerous: a study in 56 MM patients added idarubicin and CY to melphalan 200 mg/m 2 , but this was followed by a treatment-related mortality of 20% (vs 0% in the standard arm with melphalan 200 mg/m 2 ), which lead to early discontinuation of the study. 25 Another investigational strategy has been to increase the dose of single-agent melphalan to 4200 mg/m 2 with the concurrent use of the cytoprotective agent amifostine, 26,27 but data are too preliminary to justify the use of this approach in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…26 Phase I and II trials have combined highdose melphalan with other drugs, including busulfan or idarubicin, with no apparent significant improvements in outcomes. 27,28 More recently, bortezomib was combined with high-dose melphalan followed by ASCT in a phase II study. 29 The regimen was well tolerated and appeared to improve response rates when compared with historical controls (CR rate: 35% versus 11% with high-dose melphalan only; P ¼ 0.001).…”
Section: 23mentioning
confidence: 99%
“…Likewise, Anagnostopoulos et al [48] showed that a more intense regimen of thiotepa, busulfan and cyclophosphamide was not better than high dose melphalan. Fenk et al [49] showed that the addition of idarubicin and cyclophosphamide to melphalan 200 mg/m 2 increased TRM without improved survival.…”
Section: Multiple Myelomamentioning
confidence: 99%